Determinantes da mulher chefe de família brasileira: análise rural, urbana e regional - Evangelista, Márcia Maria Vieira (2020)
This work investigates the characteristics of the female head of household in Brazil, rural and urban areas, as well as the five regions of the country Brazil, using 2015 as a base compared to 2005. The microdata used come from the National Survey by Household Sample (PNAD) of the Brazilian Institute of Geography and Statistics (IBGE). As a methodology, the regression function belongs to the logit. The situations were analyzed for the variable woman head of household. The results reveal the changes in the family structure, highlighting women as an economic pillar, although still with little per capita income, making a new family situation evident. Different results were revealed depending on the region of the country, showing how eclectic these women can be depending on the Brazilian region. In summary, the work shows the socioeconomic characteristics that characterizes women to become providers of the home.